A political catechism, dedicated, without permission, to His Most Serene Highness Omar, Bashaw, Dey, and Governor, of the Warlike City and Kingdom of Algiers . the Earl of Liverpool; Lord Castlereagh, and co. /; (printed for one of the candidates for the Office of Printer to the King's Most Excellent Majesty, and sold by William Hone, 1817)
An Englishman is William Hone.